Localization of a poliovirus type 1 neutralization epitope in viral capsid polypeptide VP1. - van der Werf, S (1983)
Poliovirus type 1 cDNA sequences coding for viral capsid polypeptide VP1 were inserted into the beta-lactamase sequence of Escherichia coli plasmid pBR322. Resulting recombinant plasmid pSW119 expressed in Escherichia coli a VP1-beta-lactamase fusion protein that reacted with antibodies raised against poliovirus capsid polypeptide VP1 and with a monoclonal poliovirus type 1 neutralizing antibody, C3. Deletions of various lengths were generated within the VP1 sequence. The hybrid proteins expressed by the deleted plasmids did not react any more with C3 when the region of VP1 amino acids 95-110 (poliovirus nucleotides 2,754-2,806) was deleted. Therefore, the C3 epitope responsible for virus neutralization is most probably located in this region of the capsid polypeptide.